Receptor-Mediated Bioassay Reflects Dynamic Change of Glucose-Dependent Insulinotropic Polypeptide by Dipeptidyl Peptidase 4 Inhibitor Treatment in Subjects With Type 2 Diabetes - Yanagimachi, Tsuyoshi; Fujita, Yukihiro; Takeda, Yasutaka; Honjo, Jun; Yokoyama, Hiroki; Haneda, Masakazu (Frontiers in Endocrinology, 2020)
Objective: We recently observed a greater increase in plasma levels of bioactive glucose-dependent insulinotropic polypeptide (GIP) than glucagon-like peptide-1 (GLP-1) using the receptor-mediated bioassays in the subjects with normal glycemic tolerance (NGT) treated with dipeptidyl peptidase-4 (DPP-4) inhibitors, which may be unappreciated using conventional ELISAs during oral glucose tolerance test (OGTT). Thus, we determined incretin levels in addition to glucagon level using the bioassays in type 2 diabetes (T2DM) subjects with or without treatment of DPP-4 inhibitor, to evaluate whether these assays can accurately measure bioactivity of these peptides. Methods: We performed single meal tolerance test (MTT) by using a cookie meal (carbohydrate 75.0 g, protein 8.0 g, fat 28.5 g) in the subjects with NGT (n=9), the subjects with T2DM treated without DPP-4 inhibitor (n=7) and the subjects with T2DM treated with DPP-4 inhibitor (n=10). All subjects were fasted for 10 to 12 hours before the MTT and blood samples were collected at 0, 30, 60, and 120 min. We used the cell lines stably co-transfected with human-form GIP, GLP-1 or glucagon receptor and a cyclic AMP-inducible luciferase expression construct for the bioassays. We measured active GIP, active GLP-1 and glucagon by the bioassays. To evaluate the efficacy of bioassay, we measured identical samples via ELISA kits. Results: During the single MTT study, postprandial active GIP bioassay levels of T2DM with DPP-4 inhibitor treatment were drastically higher than those of NGT and T2DM without DPP-4 inhibitor, although the DPP-4 inhibitor-treated group showed moderate increase of active GIP ELISA and active GLP-1 bioassay. While, Active GLP-1 bioassay levels of T2DM subjects without DPP-4 inhibitor were comparable to those of NGT subjects. During the serial MTT, administration of DPP-4 inhibitor significantly increased active GIP bioassay levels, but not active GLP-1 bioassay. Conclusions: In comparison to conventional ELISA, receptor-mediated bioassay reflects dynamic change of GIP polypeptide by DPP-4 inhibitor treatment in subjects with type 2 diabetes.